Advances in molecular and cell biology . - Heppner, Gloria H.; Bittar, E. Edward (Advances in molecular and cell biology, 1993)
With the current emphasis in cancer research on oncogenes and suppressor genes, and on autocrine factors and their receptors, it is easy to conclude that the "whole story"can be read in the cancer cell per se. No one would deny that the tremendous recent advances in describing the molecular and cellular alterations in cancer cells have greatly added to our understanding of neoplasia. But, learning how to translate the meaning of these alterations into ways of treating and, better yet, preventing cancer will require at least as deep an understanding of the context in which it develops. The topics of this volume were selected to lead the reader through the complex series of events by which cancer cells and their "environment"interact to produce malignant disease. Underlying themes are the diversity in the pathways that can lead to malignancy and the basic heterogeneity of neoplastic cell populations. As has often been said, in cancer no generalizations are always true (including this one). Thus, the various chapters must be viewed as examples of possible processes and mechanisms, not as universally applicable laws.